(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2024)
This article is dedicated to the causes of the breakout of the civil war in Somalia. It also describes the issues related to humanitarian food assistance provided to thisso – called failed state by the Red Cross and UN agencies supported by international armed forces. Somalia is located in the Horn Africa, known for its strategic importance in the world. It played an essential role in the tactical game of world powers, during both the colonial era and in the Cold War. The article describes the dictatorial of Siad Barre, who served as Somali president from 1969 to 1991. His authoritarian regime led to the civil war in Somalia. The author also explains the reasons of the rise of clan animosities in the Somali ethnic group. They led to brutal internal conflict in Somalia. It resulted in the destruction of the state, ruined country and its food resources, famine and emigration of population. The article also analyzes international intervention in Somalia in 1992–1995, supported by the peacekeeping forces UNOSOM I i UNOSOM II, and UNITAF (United Task Force) operation code – named Operation Restore Hope carrying out United Nations Security Council Resolution 794. Despite many errors made by international intervening forces, both operations brought partially positive humanitarian impact.